2020
DOI: 10.1051/medsci/2020008
|View full text |Cite
|
Sign up to set email alerts
|

La réponse au stress du réticulum endoplasmique dans la physiopathologie des maladies chroniques du foie

Abstract: La prévalence des maladies chroniques du foie ne cesse d’augmenter, du fait de la pandémie de l’obésité. Ces maladies s’étendent de la bégnine stéatose à la stéatopathie non alcoolique (NASH) qui peut évoluer vers le carcinome hépatocellulaire. Il n’existe pas de traitement pour ces maladies. La transition stéatose-NASH apparaît déterminante dans leur progression. Au cours de l’obésité, l’activation chronique de la réponse au stress du réticulum endoplasmique (RE) jouerait un rôle crucial dans cette transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In addition, by enhancing inflammatory or apoptotic signalling, ERS may be another mechanism to promote NAFLD. 88,89 The experiments by Zhang et al confirmed this idea. They administered the ERS-inducing agent clathrin tunicamycin intraperitoneally to mice, which resulted in hepatic steatosis with significant increases in ERS markers, including BIP/glucose-regulated protein 78 (BIP/GRP78), CHOP and IRE1α.…”
Section: Paf-mediated Cytokine Involvement In Nafld Paf-5-ht Signalli...mentioning
confidence: 87%
“…In addition, by enhancing inflammatory or apoptotic signalling, ERS may be another mechanism to promote NAFLD. 88,89 The experiments by Zhang et al confirmed this idea. They administered the ERS-inducing agent clathrin tunicamycin intraperitoneally to mice, which resulted in hepatic steatosis with significant increases in ERS markers, including BIP/glucose-regulated protein 78 (BIP/GRP78), CHOP and IRE1α.…”
Section: Paf-mediated Cytokine Involvement In Nafld Paf-5-ht Signalli...mentioning
confidence: 87%
“…28,29 Under ER stress, released GRP78 could activate IRE1α, PERK, and ATF6, as well as their downstream signaling pathways, which promotes inflammation, apoptosis, and activity of related factors, including NF-κB, phosphorylation of eukaryotic initiation factor 2α (eIF2α), and expression of ER stress-related genes and proteins such as ATF4, c-Jun N-terminal kinase (JNK), and C/EBP homologous protein (CHOP), as well as the pro-apoptotic B-cell lymphoma-2 (Bcl-2) family member p53 up-regulated modulator of apoptosis (PUMA) and death protein 5 (DP5). [30][31][32]…”
Section: Metabolic Dysregulation Provides a Favorable Pro-inflammator...mentioning
confidence: 99%